AGE-DEPENDENT FEATURES OF EVOLVING HUMORAL IMMUNITY IN CHILDREN - A. P. Toptygina; E. L. Semikina; E. A. Kopyltsova; V. A. Alyoshkin (Медицинская иммунология, 2014)
Abstract. Age dynamics of humoral immunity was studied in healthy children, i.e., 11 newborns, 33 infants of 4 to 8 months, 32 children of 1 to 2 years old,, 17 children of 4 to 5 years old, 25 children of 6 to 8 years old, 15 children of 9 to 11 years old, and 28 adolescents of 14 to 16 years old. Evaluation of membrane receptors on B cells was performed by means of three-colour fluorescent label and allowed of characterizing B1 subpopulations (CD19+CD5+CD27-), naпve B2 cells (CD19+CD5-CD27-), and B2 memory cells (CD19+CD5-CD27+). B1 cells have been shown to dominate in blood of newborns and younger children (up to 5 years old). By the contrary, B2 memory cells were nearly undetectable in newborns, and exceeded 20% in adolescents (by 15 years old). Meanwhile, it has been revealed that the amounts of IgG1 and IgG3 subclasses did progressively increase with age, whereas IgG2 remained decreased to 50% of adult values for a long time, and reached them by 11 years and later. We suggest that the age dynamics of IgG subclasses is connected with age-dependent changes in B cell subpopulations.